ANALGESIC, ANTI-INFLAMMATORY AND ANTIPYRETIC ACTIVITIES OF THE AQUEOUS EXTRACT OF GERANIUM CAROLINIANUM L - Li, Yuan; Ye, Ying; Wang, Su-Juan; Xia, Wei; Rahman, Khalid; Yue, Wei; Zhang, Hong (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Geranium carolinianum L. (Geraniaceae) is widely used for a variety of diseases including herpetic keratitis, eczema,rheumatalgia etc. However, there is lack of relevant scientific research.Materials and Methods: GCE (125, 250, 500mg/kg body weight) was evaluated for its pharmacological properties by using the aceticacid-induced writhing test, the hot plate test and the fresh egg white-induced paw edema in rats. The dimethylbenzene-induced mouseinflammation model and the lipopolysaccharide (LPS)-induced rat fever model were employed and the acute toxicity of GCE was alsoassessed.Results: The Geranium carolinianum aqueous extract (GCE) significantly inhibited the writhing responses in mice, increased reaction time ofmice in the hot plate test, and suppressed the fresh egg white-induced paw edema in rats and the dimethylbenzene-induced ear edema in micewhilst attenuating LPS-induced fever in rats in a dose dependent manner. Furthermore, no deaths were observed when mice were orallyadministered GCE up to 14 g/kg body weight (approximately 553 times of clinical dose).Conclusions: GCE possesses analgesic, anti-inflammatory and antipyretic activities and is non-toxic at the doses used. The results of thisstudy support the clinical use and effectiveness of Geranium carolinianum as an analgesic, anti-inflammatory and antipyretic agent in folkmedicine.